Polymorphous adenocarcinoma of the salivary glands: reappraisal and update - Vander Poorten, Vincent; Triantafyllou, Asterios; Skálová, Alena; Stenman, Göran; Bishop, Justin A; Hauben, Esther; Hunt, Jennifer L; Hellquist, Henrik; Feys, Simon; De Bree, Remco; Mäkitie, Antti A; Quer, Miquel; et al. (European archives of oto-rhino-laryngology, 2018)
Although relatively rare, polymorphous adenocarcinoma (PAC) is likely the second most common malignancy of the minor salivary glands (MiSG). The diagnosis is mainly based on an incisional biopsy. The optimal treatment comprises wide surgical excision, often with adjuvant radiotherapy. In general, PAC has a good prognosis. Previously, PAC was referred to as polymorphous low-grade adenocarcinoma (PLGA), but the new WHO classification of salivary gland tumours has also included under the PAC subheading, the so-called cribriform adenocarcinoma of minor salivary glands (CAMSG). This approach raised controversy, predominantly because of possible differences in clinical behaviour. For example, PLGA (PAC, classical variant) only rarely metastasizes, whereas CAMSG often shows metastases to the neck lymph nodes. Given the controversy, this review reappraises the definition, epidemiology, clinical presentation, diagnostic work-up, genetics, treatment modalities, and prognosis of PAC of the salivary glands with a particular focus on contrasting differences with CAMSG.
Keywords: Cribriform adenocarcinoma of minor salivary glands; Salivary Gland Neoplasms; adenokarcinom; Humans; Adenocarcinoma; Pathology; Polymorphous adenocarcinoma; Polymorphous low-grade adenocarcinoma; Salivary glands; Salivary Glands, Minor; Therapy; malé slinné žlázy; lidé; prognóza; nádory slinných žláz; Prognosis